A systematic review on the impact of teacher professional development on digital instructional integration and teaching practices - Amemasor, Stephen Kwashie; Oppong, Stephen Opoku; Ghansah, Benjamin; Benuwa, Ben-Bright; Essel, Daniel Danso (Frontiers in Education, 2025)
This systematic review examines the influence of teacher professional development (TPD) programs on teachers’ attitudes toward digital instructional integration (DII). By analyzing 23 peer-reviewed studies published between 2020 and 2024, this study explores the key components of effective TPD programs and their impact on digital instructional practices. The review follows the PRISMA framework, detailing a structured selection process, including database searches, inclusion and exclusion criteria, and a rigorous qualitative synthesis of findings. Results indicate that effective TPD programs share key characteristics, including collaborative learning environments, hands-on digital training, ongoing mentorship, and institutional support. These elements foster positive shifts in teachers’ attitudes, confidence, and competencies regarding DII. The study highlights the need for sustained and context-specific professional development initiatives beyond one-time training sessions to ensure meaningful and long-term integration of digital tools in education. This review contributes to the field by providing evidence-based insights into designing and implementing impactful TPD programs. Its findings inform policymakers, educators, and professional development providers on structuring TPD to maximize digital instructional integration. Future research should explore the longitudinal impacts of TPD on teaching efficacy and student outcomes in technology-enhanced learning environments.